1986
DOI: 10.1007/bf00237745
|View full text |Cite
|
Sign up to set email alerts
|

European vestibular experiments on the Spacelab-1 mission: 7. Ocular counterrolling measurements pre- and post-flight

Abstract: The static ocular counterrolling (OCR) of the four scientific crew members in the first Spacelab mission was measured during baseline-data-collection before and after the flight of SL-1. It was presumed that the modification of otolithic responses during spaceflight will be reflected in specific changes of the OCR-gain on the first days after recovery. The magnitude of OCR was determined analysing colour-transparencies of subjects right eyes that were produced in different positions of lateral body tilt. In ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(15 citation statements)
references
References 9 publications
2
12
1
Order By: Relevance
“…Similar to aged subjects, remodeling of synaptic connections in vestibular sensorial hair cells and an increase in the number and the size of synaptic knobs have been reported in adult rats during shortterm space missions [111,112]. The vestibulo-spinal and vestibulo-ocular reflexes are also altered in these conditions [113][114][115].…”
Section: Does Vestibular Aging Contribute To Osteoporosis?mentioning
confidence: 93%
“…Similar to aged subjects, remodeling of synaptic connections in vestibular sensorial hair cells and an increase in the number and the size of synaptic knobs have been reported in adult rats during shortterm space missions [111,112]. The vestibulo-spinal and vestibulo-ocular reflexes are also altered in these conditions [113][114][115].…”
Section: Does Vestibular Aging Contribute To Osteoporosis?mentioning
confidence: 93%
“…Hence this work would benefit from future parabolic flight experiments that test, for example, in Lunar and Martian g-levels. Thirdly, previous investigators have found an interesting relationship between the magnitude of ocular misalignments in novel g-levels and motion sickness (both parabolic flight motion sickness and SMS) (Kornilova et al, 1983 ; Vogel and Kass, 1986 ; Lackner et al, 1987 ; Diamond et al, 1990 ; Diamond and Markham, 1991 , 1992b ). Since none of our non-astronaut subjects experienced adverse symptoms inflight, we could not compare their ocular misalignments to motion sickness susceptibility.…”
Section: Discussionmentioning
confidence: 93%
“…We investigated this further by looking for similar trends from previous investigators, but did not find anything conclusive. For example, Vogel and Kass' four crewmembers all showed higher OCR gains during leftward tilts preflight and during rightward tilts post-flight (Vogel and Kass, 1986 ). Diamond and colleagues, however, found the opposite result in seven non-astronaut subjects: larger OCR was observed during rightward tilts than leftward tilts, and the depressed eye torted more than the elevated eye (Diamond et al, 1979 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations